Al-Muassasaat al-Nasyiah fi Aljazair fi al-Tanmiyah al-Iqtishadiyah: Ma'ayir al-Najah wa Subul al-Tathawwur - Sayah, Nadia (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
It can be said at the beginning that the economy is the basis of life and the construction of the earth, and because it is so, it is necessary to know its goals, and determine its foundations and principles, which are in line with the teachings of the Islamic religion through its provisions regulating economic life, and this places on the shoulders of institutions a very great responsibility, from their inception until their attainment. Glory and the pinnacle of success. Today's economy has also become obligated to keep pace with what has resulted from globalization and new developments at all levels, and it is also obligatory for us - the state, institution and individual - to develop thinking and keep pace with the situation, and to search for a solution that eliminates unemployment or reduces its spread among members of society, as well as exploiting competencies and ideas in investment projects. It is supported by the state through its various financial institutions, or established by the individual based on his independent financial resources. That's the start-up. Therefore, through this research paper, we are trying to shed light on the emerging institutions in Algeria and their role in economic development, and we examine their nature, characteristics, advantages, types, the extent of their impact on the individual and society, and what are their components that guarantee their survival and continuity? Finally, let us conclude that the innocence and importance of the idea is not the only condition for the success of the emerging project; The project leader must avoid common mistakes that could lead to a decline in the performance of his project, such as failure to retain ideas properly, or failure to implement ideas in an appropriate manner, thus wasting time and resources. The entrepreneur is also supposed to be fully aware of the nature of The challenges that he may face, whether they are internal challenges in a disharmonious work environment, or external challenges in light of the intense competition between companies. This awareness is what will qualify the emerging project owner to deal with challenges with great flexibility and take advantage of existing opportunities. The Islamic economy is also based on economic freedom governed by Sharia values and morals, and is also based on social solidarity, including the obligatory or desirable areas of spending that it has legislated.